Financial Management Of Msme In Culinary Industry According To Demographics And Financial Literacy - Caecilia Wahyu Estining Rahayu; Christina Heti Tri Rahmawati (Soegijapranata Catholic University, 2022)
The aim of this study is to scrutinize how Micro, small, and medium-sized enterprises (MSME) in the culinary industry manage their finances according to demographics and financial literacy. A number of MSMEs in the culinary field operating in Catur Tunggal Village, Depok District, Sleman Regency, Special Region of Yogyakarta was used as the sample which were selected using non-random sampling. Questionnaire was the instrument to collect data from the respondents and Chi Square analysis was employed as the data analysis technique. This study revealed that age and financial literacy of the MSME actors correlate partially with financial management. However, monthly income and educational level have no correlation with financial management. This results suggest that MSME actors can manage their business finances better if their financial literacy (knowledge) improves. As a result, they can maintain their business and enhance their standard of life.